Analysis and diagnosis of nitrogen nutrition in durum wheat for the design of a nitrogen fertilizer grid in the semi-arid region - Douniazed C.; Amor H. (Research and innovation as tools for sustainable agriculture, food and nutrition security, 2020)
Improving the efficiency of nitrogen use by crops has become imperative in the current and future economic and environmental context. Nitrogen fertilization is often considered as the practice with the greatest impact on crop growth. However, optimizing its management is highly dependent on soil conditions and intra- annual climatic achievements. The fractionation of nitrogen fertilizer inputs is a relevant approach to better match crop needs with nitrogen supplies. Nitrogen fertilization strategies that combine the fractionation of the total recommended agricultural plot-scale with the assessment of the nitrogen requirement during the growing season can greatly help to better match nitrogen requirements and supplies. This will increase the efficiency of nitrogen use of the applied fertilizer. The final objective of these strategies is to assist in deciding whether to apply complementary nitrogen fractions and how much nitrogen to apply. It may be easier to look at the crop itself as an indicator of its nitrogen requirement. In fact, the biomass produced is often considered to integrate well the effects of conditions occurring during the growing season. The objective of this work carried out over several years on several sites in different regions where we have chosen, in this article the site of the region of El-outaya for a single 2016/2017 agricultural campaign, is to study the effects of different fractionation of a rate of 69 NU per hectare on aerial biomass, 1000 grain weight, grain yield, grain protein content, dry matter nitrogen content and chlorophyll content durum wheat to establish a nitrogen fertilizer grid in the semi-arid region. The results obtained showed highly significant effects on all the parameters studied. This study confirms that a dose of 69 units of nitrogen, applied in two fractions (Df) distributed 2/3 at tillering and 3/4 at the stage of 1cm spike improves all the parameters studied compared to the control (Dt) and the dose made in the tillering stage (D0). The chlorophyll content recorded in (Df) indicates that the plant is well fed with nitrogen, so it is not interesting to use another fraction of nitrogen, knowing that the protein is not valued at this time in Algeria.
2. MEDFORUM 2018, 2018/09/18-20, Bari (Italy)